Advances in Ecohydrology in Arid Inland River Basins (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint aims to guide readers in exploring research and applications in ecological hydrology for arid inland river basins. From analyzing climate change impacts on water cycles to constructing ecological–hydrological models, assessing drought conditions, and advancing ecological restoration with efficient water resource utilization, we comprehensively examine the application potential of these cutting-edge technologies in arid regions. In this Reprint, leading experts share their research findings and future perspectives, deepening our understanding of ecological–hydrological interactions, environmental risks, and sustainable management practices in changing arid landscapes. These studies integrate hydrological process research into ecological management and water optimization, driving advancements in arid area ecohydrology and fostering interdisciplinary collaboration. They also provide crucial support for sustainable water resource management.